Calcifying epithelial odontogenic tumor: Report of two cases - Mandal Shramana; Varma Kachnar; Khurana Nita; Mandal A (Wolters Kluwer Medknow Publications, 2008)
Calcifying epithelial odontogenic tumor (CEOT) is a rare, benign odontogenic tumor. It constitutes 0.4-3% of all odontogenic tumors. There is only a single case, which has been reported in the Indian literature that too in cytology. Microscopically, these are composed of large sheets of epithelial cells, amorphous amyloid-like material and calcification. Although these lesions are benign, they can be locally aggressive, but malignant transformation and metastasis is rare. Considering its locally aggressive nature, appropriate management and long-term follow-up is recommended. We describe two cases of CEOT involving the hard palate and leading to facial alterations.